The Impact of Tax Incentives on the New Quality Productivity of Enterprises - based on Data Analysis of Chinese A-share Listed Companies - Ma, Weiyi (Journal of Global Economy, Business and Finance, 2025)
Tax incentives, as an important means for the state to conduct macro-control, play a great role in stimulating the development of new quality productivity of enterprises. Based on the data of A-share companies in Shanghai and Shenzhen from 2015 to 2023, this paper uses a two-way fixed effect model to empirically study the impact of tax incentives on the new quality productivity of enterprises, and conducts heterogeneous analysis according to the nature of equity, industry and region. The research shows that tax incentives have a significant positive impact on the new quality productivity of enterprises, but the incentive effect of tax incentives on the new quality productivity of enterprises varies significantly among enterprises with different equity natures, different industries and different regions.